Evaluation and Improvement of E-Grocery Mobile Application User Interface Design Using Usability Testing and Human Centered Design Approach - Glisina Dwinoor Rembulan; Pas Mahyu Akhirianto; Dedit Priyono; Dendy K. Pramudito; Dedy Irwan (Jurnal Sistim Informasi dan Teknologi, 2023)
This study aims to determine the usability value of the e-grocery application interface design before and after repairs are carried out and provide recommendations for interface improvement designs using the Human-Centered Design (HCD) approach. The usability testing method and the system usability scale questionnaire are used to evaluate usability. The usability evaluation and design improvements to the e-grocery application have increased the effectiveness value of lower than 20% and an efficiency value of lower than 30%, with the task processing time needed by respondents being faster and improved by more than 900 seconds. And the value of satisfaction with the SUS score for the improvement design evaluation has increased, with a score difference of 30 points from the SUS score for evaluating e-grocery applications.